LONG-TERM TREND OF BLADDER CANCER MORTALITY IN SERBIA, 1991-2024: A JOINPOINT REGRESSION ANALYSIS - Ilić, Irena; Ilić, Milena (HEALTH CARE, 2025)
Introduction/Aim: Bladder cancer is among the main urological diseases. Bladder cancer mortality trends vary significantly worldwide. This research sought to assess temporal trends in deaths due to bladder cancer in Serbia. Methods: This was a population-based descriptive epidemiological study. Bladder cancer mortality data were obtained from an official database. Direct standardization with the World standard population was used to compute the age-standardized rates (ASRs) per 100,000. Joinpoint regression analysis was employed to assess temporal trends in bladder cancer mortality using the average annual percentage change (AAPC) alongside its 95% confidence interval (95% CI) over the 1991-2024 period. Results: During the period 1991-2024, almost 20,000 deaths due to bladder cancer (about 15,000 among men and 5,000 among women) occurred in Serbia. Average annual ASR of mortality from bladder cancer was notably higher among males than females (5.94 versus 3.87 per 100,000, respectively). Significant increases in bladder cancer mortality trends were recorded for both males (AAPC=0.6%; 95% CI=0.4 to 0.9) and females (AAPC=1.3%; 95% CI=1.0 to 1.5). The male and female trends were not parallel, as the final selected model rejected parallelism (p = 0.008). A significant increase in bladder cancer mortality in women was recorded in middle age (age groups 55 to 69 years), while in men a more pronounced increase was observed in older people (age groups 70 and older). Conclusion: An increase in bladder cancer mortality during more than three decades in Serbia implies that further analytical research is needed.